Surface properties and hardness of polypropylene composites filled with sunflower stalk flour - Alperen Kaymakci (BioResources, 2013)
The effects of agricultural flour content on surface roughness, wettability, and surface hardness of injection molded polypropylene (PP) composites was investigated. Four content levels of the waste sunflower stalk flour (WSF) were mixed with the PP with and without maleic anhydride grafted PP (MAPP) as a coupling agent. Contact angle measurements were performed using a goniometer connected with a digital camera. Three roughness parameters, average roughness (Ra), mean peak-to-valley height (Rz), and maximum roughness (Rmax), were used to evaluate surface roughness. The surface roughness increased with increasing WSF content while their wettability decreased. The unfilled (neat) PP composites had the lowest surface roughness, while the roughest surface was found for the PP composites filled with 60 wt% WSF. The surface smoothness of the composites was noticeably increased by addition of the compatibilizer MAPP while the wettability was decreased. The scratch hardness of the PP composites increased significantly with increasing WSF. The incorporation of the coupling agent increased the scratch hardness of the specimens. The Brinell hardness increased with increasing filler loading. At similar filler loading the composites with MAPP had lower Brinell hardness value than those without MAPP.